From Disparity to Belonging: The Role of Inter-Ethnic Friendship in Migrant Students Adaptation in Central Java and Yogyakarta - Fadhil Maliky Islah; Riza Akhdisholikhah (Fakultas Psikologi, Universitas Islam Negeri (UIN) Sunan Gunung Djati Bandung, 2026)
This study aimed to explore how inter-ethnic friendship are initiated and sustained among migrant students in Java, and the effect on social adaptation and identity negotiation. Using a qualitative design, in-depth interviews were conducted with 18 students from diverse ethnic backgrounds who had migrated to Java for higher education. The results showed that thematic analysis identified four major themes, namely (1) migration, educational inequality, and the opportunity for encounter, (2) the “frog in a shell” relationship and conditional friendship, (3) social skills in identity negotiation, and (4) alien guests vs. guests at home. Despite initial barriers, participants demonstrated openness, empathy, and a shared national identity that allowed for significant cross-ethnic relationships. Inter-ethnic friendship were found to facilitate social inclusion, personal growth, and deeper appreciation of cultural diversity. In conclusion, this study contributes to a better understanding of how students navigate intergroup boundaries and transform educational migration into opportunities for unity in a plural society.